2007
DOI: 10.1002/bdd.582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on the intravenous and oral pharmacokinetics of verapamil in rats

Abstract: The present study aimed to investigate the effect of atorvastatin on the intravenous and oral pharmacokinetics of verapamil in rats. The pharmacokinetic parameters of verapamil were measured after an oral (9 mg/kg) or intravenous (3 mg/kg) administration of verapamil to rats in the presence and absence of atorvastatin. Compared with the control given verapamil alone, the concurrent use of 1.5 mg/kg of atorvastatin significantly increased the oral exposure of verapamil in rats. The AUC and C(max) of verapamil i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…nicardipine, suggesting that atorvastatin did not inhibit the metabolism of nicardipine via hepatic CYP3A subfamily and renal excetion in rats. This result appeared to be consistent with a previous report that oral administration of atrovasatatin significantly increased the oral bioavailability of verapamil in rats (Choi et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…nicardipine, suggesting that atorvastatin did not inhibit the metabolism of nicardipine via hepatic CYP3A subfamily and renal excetion in rats. This result appeared to be consistent with a previous report that oral administration of atrovasatatin significantly increased the oral bioavailability of verapamil in rats (Choi et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Calcium-channel blockers increased plasma concentrations of some statins (lovastatin, pravastatin and simvastatin), possibly through the inhibition of CYP 3A4 and P-gp (Azie et al, 1998;Mousa et al, 2000). But there are fewer reports about the effects of HMG-CoA reductase inhibitors on the bioavailability or pharmacokinetics of calcium channel antagonists in rats (Choi et al, 2006;Choi et al, 2008). Moreover, atorvastatin and nicardipine could be prescribed for the prevention or treatment of cardiovascular diseases as a combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are some papers that the results obtained in vivo in rats could be extrapolate on humen from results obtained in vitro with human CYP3A4 and P-gp. As CYP3A9 expressed in rat corresponds to the ortholog of CYP3A4 in human [27,42,43], and rat CYP3A2 is similar to human CYP3A4 [29,30,44]. Human CYP2C9 and 3A4 and rat CYP2C11 and 3A4 are 77% and 73% homologous, respectively [31,32,45].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium-channel blockers increase the plasma concentrations of some statins, possibly through the inhibition of CYP 3A4 and P-gp [27,28]. However, few studies have reported about the effects of HMG-CoA reductase inhibitors on the bioavailability or pharmacokinetics of antihypertensive agents [29][30][31][32]. Although a combination of nifedipine and statins have been clinically prescribed for treatment of hypertension, the pharmacokinetic interaction between a HMG-CoA reductase inhibitor and nifedipine in vivo has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…2). As amlodipine is an inhibitor of CYP3A4, con- www.biomolther.org comitant use of the drug might play a role in the wide inter-individual variability in the response to drugs (Choi et al, 2006;Choi et al, 2008). Most calcium channel blockers (verapamil, nifedipine, diltiazem, barnidipine) also have inhibitory effect on the drug transporter P-gp, which mediates drug's intestinal absorption (Yusa and Tsuruo, 1989;Wacher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%